1998
DOI: 10.1021/ja983091x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for the DNA Sequence Selectivity of Ecteinascidin 736 and 743:  Evidence for the Dominant Role of Direct Readout via Hydrogen Bonding

Abstract: The marine natural product ecteinascidin 743 (Et 743) is currently in phase II clinical trials. We have undertaken parallel structural and modeling studies of an Et 743−(N2-guanine) 12-mer DNA adduct and an adduct involving the structurally related Et 736 of the same sequence in order to ascertain the structural basis for the ecteinascidin−DNA sequence selectivity. In contrast to the C-subunit differences found in Et 736 and Et 743, they have identical A−B-subunit scaffolds, which are the principal sites of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
81
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 15 publications
5
81
0
Order By: Relevance
“…Gel shift assays combined with high-field NMR have demonstrated that the alkylation of ET-743 occurs at guanines located either in the sequence 5′-PuGC-3′ or 5′-PyrGG-3′ [10][11][12][13]. Other adducts are formed, but are less stable and are reversible [12][13][14], suggesting that, after prolonged exposure, ET-743 would be released from these less stable adducts and a progressively higher percentage of ET-743 would be found bound to guanines located in the frame of bases conferring high thermodynamic stability. The reported structural changes induced by ET-743, such as widening of the minor groove and bending of DNA toward its major groove, could be important in affecting the recognition and binding of transcription factors or DNA-binding proteins (e.g., DNA repair proteins).…”
Section: Binding To Dnamentioning
confidence: 99%
See 1 more Smart Citation
“…Gel shift assays combined with high-field NMR have demonstrated that the alkylation of ET-743 occurs at guanines located either in the sequence 5′-PuGC-3′ or 5′-PyrGG-3′ [10][11][12][13]. Other adducts are formed, but are less stable and are reversible [12][13][14], suggesting that, after prolonged exposure, ET-743 would be released from these less stable adducts and a progressively higher percentage of ET-743 would be found bound to guanines located in the frame of bases conferring high thermodynamic stability. The reported structural changes induced by ET-743, such as widening of the minor groove and bending of DNA toward its major groove, could be important in affecting the recognition and binding of transcription factors or DNA-binding proteins (e.g., DNA repair proteins).…”
Section: Binding To Dnamentioning
confidence: 99%
“…This observation prompted us to speculate that this part of the molecule is crucial for the mechanisms responsible for the antitumor activity. According to the model proposed by Hurley and coworkers [11,12,14], it seems that a C subunit not bound to DNA but projecting out from the minor groove might be able to interfere with DNA-binding factors. This hypothesis led us to investigate whether transcription factors that bind to DNA were inhibited by ET-743, which also binds to DNA [15].…”
Section: In Vitro Interference Of Et-743 With Dna-binding Proteins Anmentioning
confidence: 99%
“…Interactions of ecteinascidins with DNA have been proposed on the basis of structural similarities with other tetrahydroisoquinoline-containing antibiotics, biochemistry, x-ray crystallography, NMR spectroscopy, and molecular modeling data (2,5,(7)(8)(9). The pattern of potential hydrogen bond acceptors and donors indicates that the drug is likely to bind to the DNA minor groove (5,8,9).…”
mentioning
confidence: 99%
“…The pattern of potential hydrogen bond acceptors and donors indicates that the drug is likely to bind to the DNA minor groove (5,8,9). Et743 contains a carbinolamine center at the N2 position, and elimination of the adjacent hydroxyl group (at position 21) results in a Schiff base vulnerable to nucleophilic attack, leading to DNA alkylation (Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation